Parasitological aspects of wild ungulate acclimatization and introduction - A. N. Pelgunov; L. P. Maklakova (Российский паразитологический журнал)
Long-term monitoring and literary data on the effect of wild ungulate acclimatization and introduction on territory helminth fauna complex are reviewed. It is shown that in several cases introduced wild ungulates may lose their specific parasites and aquire indigenous ones thus maintaining foci of native parasitic diseases. Brought with introduced animals new parasites colonize new hosts and inflict significant losses to game management.